1979
DOI: 10.1172/jci109344
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Acetone Metabolism in the Fasting Human

Abstract: A B S T R A C T The metabolism of acetone was studied in lean and obese humans during starvation ketosis. Acetone concentrations in plasma, urine, and breath; and rates of endogenous production, elimination in breath and urine, and in vivo metabolism were determined. There was a direct relationship between plasma acetone turnover (20-77 ,Umol/m2 per min) and concenitration (0.19-1.68 mM). Breath and urinary excretion of acetone accounted for a 2-30% of the endogenous production rate, and in vivo metabolism acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
1
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 18 publications
(21 reference statements)
7
83
1
1
Order By: Relevance
“…The extent of inhibition by imidazole in vitro of the cytochrome P-&O-dependent acetone oxidation correlated well with the findings in vivo regarding the ability of imidazole, at similar concentrations, to prevent the incorporation of ['4C]acetone into low-M, carbohydrates, such as glucose. The apparent J&,, of the reaction in microsomes of about 0.9 mM is lower than the acetone concentrations in plasma reported under starvation and conditions of ketoacidosis [7,8].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The extent of inhibition by imidazole in vitro of the cytochrome P-&O-dependent acetone oxidation correlated well with the findings in vivo regarding the ability of imidazole, at similar concentrations, to prevent the incorporation of ['4C]acetone into low-M, carbohydrates, such as glucose. The apparent J&,, of the reaction in microsomes of about 0.9 mM is lower than the acetone concentrations in plasma reported under starvation and conditions of ketoacidosis [7,8].…”
Section: Discussionmentioning
confidence: 74%
“…The plasma concentrations of acetone in such subjects are in the range l-10 mM [7,8]. At the smaller acetone concentration, 75% of the acetone produced is metabolized in vivo, especially to glucose [8].…”
Section: Introductionmentioning
confidence: 99%
“…In our previou·3 study on acetone in man the uptake during 2 h of exposure was 8-16 mg/kg (0.14-0.28 mmol/kg) and the amount exhaled [16][17][18][19][20][21][22][23][24][25][26][27] Ofo of the uptake (21). In this present 3tudy with mice about 52 Ofo of the expired radioactivity after concluded exposure was unmetabolized acetone, and the remaining part carbon dioxide.…”
Section: Discussionmentioning
confidence: 99%
“…The acetone concentration correlates with the concentration of blood ß-hydroxybutyrate (Reichard et al 1979;Yamane et al 2006). The kinetic responses of ketone bodies to exercise is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…Acetone is mainly generated from non-enzymatic, decarboxylation of acetoacetate (Laffel et al 1999;Owen et al 1982). Ketones in blood increased gradually with respect to the length of fasting periods in diabetics and obese people (Tassopoulos et al 1969;Reichard et al 1979). Owen et al (1982) demonstrated that in diabetic patients, plasma acetone concentration is significantly related to breath acetone concentration.…”
Section: Introductionmentioning
confidence: 99%